Final times (Journal of Parents and Teachers, 1995)
It addresses the interaction of numbers with the end times, emphasizing their spiritual significance. The importance of confession in this context is mentioned. It reflects on how these elements influence the current perception.
Keywords: interaction; numbers; spiritual significance; confession